Study of Government Policy in the Lisu Massikola Community Movement Program in Bone Regency - Paikah, Nur (Institut Agama Islam Negeri (IAIN) Kendari, 2023)
Although government policies play an important role in improving education and IPM, maximizing overcoming the APS phenomenon, there is evidence of government efforts to transform even though these policies still need to be evaluated. Therefore, this study aims to reveal and evaluate the GEMAS LIMAS program policy in Bone Regency in terms of education design in overcoming APS. The research method used, sociolegal research with a conceptual approach, and data collection with direct interviews with policy makers related to this APS education program. The findings of the research are: first, the GEMAS LIMAS program is one of the strategies to overcome the education sector and human index development. Second, the financial sector and budget allocation are limited in maximizing the GEMAS LIMAS program. Third, there are gaps and inconsistencies in APS data from relevant agencies in Bone district.